A Simulation Technique for Wireless Mesh Networks to Present Its Topology and Evaluate Its Impact on Communication Revolution - Alahdal, Ahmed; Shinde, G. N. (Scientific Research Publishing, 2016)
The topology of full Mesh has driven the Researchers in the field of wireless communication to claim that wireless mesh networks can be a significant change in the future of wireless communication. This paper presents a simulation process using Mesh routers which simulate wireless mesh network with multiple values to investigate its performance and how results can be optimized in such experience. During the process, we expand the area by assigning different values according to the number of routers needed for implementation. We create a proper centralized connectivity with more and less number of nodes using IEEE802.11a and g as a backbone and source of internet. We also study and observe its topology which provides multiple interfaces and paths between endpoints as well can control, self heal, configure and organizes itself.
Keywords: WMNs; Wireless Communication; Mesh Router; IEEE802.11a & g